La cestería decorada de la cueva de los Murcíélagos (Albuñol, Granada) - Cacho Quesada, Carmen; Alonso Mathias, Férnan; Papí Rodes, Concepción; Sánchez Barriga Fernández, Antonio (Complutum, 1996)
Sin resumen